MORREMOS TODOS: ATITUDES DIANTE DA MORTE (SAO S AO P AULO, SÉCULO XVII) ) - Alves, Marilia Tofanetto [UNESP] (Univ Federal Rio Grande Sul, Programa Pos-graduacao & Historia, 2024)
The history outlined here aims to analyze the attitudes towards a moment essentially hard to the lives of seventeenth-century Christian men - death. These behaviors will be investigated based on documentation in which individuals, by their own hands, proposed to take action about themselves and their own when close to the last moment. It's about the wills. We will examine the text of the last wills of characters from S & atilde;o Paulo, seeking to ascertain an equally apparent perception in the well-dying manuals that warned about the transpass: the notion of individual responsibility to be saved. Furthermore, by registering the last wishes of Catholics, we will focus on the contours of the incipient domestic feeling present in Portuguese America in the 17th century in a timid, but continuous, hardening.
Keywords: Death; Wills; Family